Long-term evaluation of the sape of the rconstructed daphragm in ptients with left-sided congenital diaphragmatic Hernia using serial chest radiographs and correlation to further complications - Schrottenberg, Christoph von; Lindacker, Maren; Weis, Meike; Büttner, Sylvia; Schaible, Thomas; Boettcher, Michael; Wessel, Lucas; Zahn, Katrin (Journal of Clinical Medicine, 2024)
Background: Defining risk factors for long-term comorbidities in patients after neonatal repair of congenital diaphragmatic hernia (CDH) is an important cornerstone of the implementation of targeted longitudinal follow-up programs. Methods: This study systematically assessed serial chest radiographs of 89 patients with left-sided CDH throughout a mean follow-up of 8.2 years. These geometrical variables for the left and right side were recorded: diaphragmatic angle (LDA, RDA), diaphragmatic diameter (LDD, RDD), diaphragmatic height (LDH, RDH), diaphragmatic curvature index (LDCI, RDCI), lower lung diameter (LLLD, RLLD) and thoracic area (LTA, RTA). Results: It was demonstrated that the shape of the diaphragm in patients with large defects systematically differs from that of patients with small defects. Characteristically, patients with large defects present with a smaller LDCI (5.1 vs. 8.4, p < 0.001) at 6 months of age, which increases over time (11.4 vs. 7.0 at the age of 15.5 years, p = 0.727), representing a flattening of the patch and the attached rudimentary diaphragm as the child grows. Conclusions: Multiple variables during early follow-up were significantly associated with comorbidities such as recurrence, scoliotic curves of the spine and a reduced thoracic area. Some geometrical variables may serve as surrogate parameters for disease severity, which is associated with long-term comorbidities.
Gesehen am 10.10.2024